Makna Tari Pegawai Dalam Pesta Perkawinan Di Kampung Hulu Pasa Malintang Nagari Inderapura Tengah Kecamatan Pancung Soal Kabupaten Pesisir Selatan - Febri Susanti; Nerosti Nerosti (FBS Universitas Negeri Padang, 2020)
This research aims to reveal and discuss the Meaning of Pegawai Dance in a Marriage Party in the Kampung Hulu Pasa Malintang, Nagari Inderapura Tengah, Pancung Soal, Pesisir Selatan District. This research is a qualitative research using analytical descriptive method. The Main Instrument was the researcher itself with primary and secondary data types. The data collection techniques were literature review, observation, interview and documentation. The object of research was the Pegawai Dance in KampungHuluPasaMalintang, Nagari Inderapura Tengah, Pancung Soal, Pesisir Selatan District. The results of this study indicate that the meaning of Pegawai Dance in a marriage party in the village of Kampung Hulu Pasa Malintang Nagari Inderapura Tengah can be analyzed from three aspects: (1) Bride and groom who stand at the aisle, in their own positions, holding a shawl that forms a swing. The shawl is tied in both thumbs of the bride and the groom. This means that both are ready to tie the relationship as a husband and wife and hope to get a good offspring.(2) Dancers who move (a) LangkahPanjang (long steps)means to see the bride and groom's descendants. (b) SeroangKanan (a right turn)means to seethe swingto keep it not to tilt so the bride is more careful and maintains domestic relations. (c)Seroang Kiri (a left turn) has the same meaning as the right one.(d) Ninjau (a review) meansto keep the position of the swing to be always in the middle so that the bride and groom work together and help each otherin difficulties and happiness as well as complement each other. (3) From the music lyric, it contains parents' prayers for their children so they can live a good marriage life and are blessed by God. Generally, the performance of the Pegawai Dance at a wedding can be seen as a manifestation of life values about responsibility and cooperation in carrying out the household ark, including giving a gala (a title) to the groom to equalize his status with the bride's so that he is respected by the bride family